Survey on Research Progress of Load Balancing in LTE-Advanced Heterogeneous Network - Juanxiong Xu; Yisha Liu; Lun Tang; Qianbin Chen (Dianxin kexue)
With next-generation mobile communication networks evolving to high dense, amorphous and heterogeneous network, matching the demand for business with the supply of resources has been one of the challenging problems of resource management in heterogeneous network（HetNet）, namely load balancing problem. The general load balancing problems are formulated. Following that, a comprehensive taxonomic approach to classifying algorithms of load balancing was proposed, based on which detailed analyses and thorough comparisons for the main strategies in recent years were made; and several schemes to reduce signaling overhead were compared and analyzed in the load balancing process. Finally, research results were summarized, and some new issues in load balancing strategies conforming to the trends to be further studied were pointed out.